The constitutions that shaped us : a historical anthology of pre-1867 Canadian constitutions - Gagnon, Alain; Laforest, Guy, 1955-; Tanguay, Yves, 1955-; Brouillet, Eugénie, 1973- (McGill-Queen's University Press, 2015)
"The Constitutions that Shaped Us is part of a broader project to re-examine, from a comparative and critical standpoint, the events (Charlottetown Conference of 1864, Quebec Conference of 1864, and a formal meeting in London in 1866 which led to the passage of the British North America Act in 1867, key players (John A. MacDonald, George-Etienne Cartier, D'Arcy McGee, and Alexander Galt to name but a few), and texts (the Royal Proclamation of 1763, the Quebec Act of 1774, the Constitutional Act of 1791, and the Act of Union of 1840) that led to the union of several British colonies in North America between 1864-1867. The anthology was first published in French by Presses de l'Université Laval and endeavours to give readers a critical and pluralist collection by providing a serious and in-depth telling of the events leading to the union of British colonies, the birth of the Dominion of Canada, and the re-birth of political autonomy in a colony known successively as Quebec, Lower Canada, Canada East and once again Quebec in 1867"--